Blood and Ink! The Common-Interest-Game Between Terrorists and the Media - Bruno S. Frey; Dominic Rohner (Center for Research in Economics, Management and the Arts (CREMA), 2006)
It has often been pointed out in the literature that a symbiotic relationship exists between terrorist groups and the media. As yet, however, no formal model has been built based on this issue and only very little empirical research has been done in this field. The present contribution builds a simple game theoretic model, focussing on the social interactions between terrorists and the media. The model has features of a common-interest-game and results in multiple equilibria. After a discussion of the policy implications of the model, an empirical analysis is performed. Using newspaper coverage, terror incidents and terror fatalities data, it is shown that media attention and terrorism do mutually Granger cause each other, as predicted by the model. Moreover, it is explained why terror attacks tend to be ?bloodier? in developing countries than in Europe and the United States.
Keywords: C72; D74; H52; H77; J22; 330; Terrorism; media; common-interest-game; coordination; conflict